Herbivore intraguild interactions decrease ectoparasitoid Bracon nigricans parasitism of Phthorimaea absoluta and responses to tomato volatiles - Fiaboe, Kokou Rodrigue; Yusuf, Abdullahi Ahmed; Torto, Baldwyn; Khamis, Fathiya Mbarak (Frontiers in Ecology and Evolution, 2023)
Intraguild interactions are known to trigger competition among phytophagous insects that depend on the same food source, which may have implications on natural enemy performance. Here, we tested the hypothesis that intraguild interactions between the greenhouse whitefly, Trialeurodes vaporariorum, and the South American tomato pinworm, Phthorimaea absoluta on the host plant tomato would affect performance of the pinworm ectoparasitoid Bracon nigricans. In oviposition bioassays, P. absoluta females significantly laid more eggs and were attracted to tomato plants infested with T. vaporariorum than uninfested plants. Additionally, T. vaporariorum infestation decreased B. nigricans parasitism on P. absoluta larvae and attraction to tomato plants. In coupled gas chromatography-electroantennographic detection (GC-EAD) recordings, antennae of P. absoluta and B. nigricans females detected 18 and 15 components, respectively from the herbivore-induced volatiles, which were identified by GC-mass spectrometry (GC-MS) as green leaf volatiles (GLVs) and terpenes. In dose-response behavioral assays, P. absoluta and B. nigricans responses varied with the composition and concentration of blends and individual compounds tested. Whereas P. absoluta was attracted to GLVs and terpenes, B. nigricans avoided most of these chemicals, especially the GLV (E)-2-hexenal and terpenes δ-3-carene, and (E)-caryophyllene. The results suggest that herbivore intraguild interactions can influence the behavioral ecology and performance of natural enemies which may have evolutionary significance. Also, these specific GLVs and terpenes can be exploited in the management of P. absoluta.